Influences of lead and magnesium co-doping on the nanostructural, optical properties and wettability of spin coated zinc oxide films. (November 2015) - Shaban, Mohamed; El Sayed, A.M.
Abstract: The quality and optical homogeneity of thin films are necessary for optoelectronic devices and semiconductor technology. The influence of Pb doping, Zn1− x Pb x O (0≤ x ≤0.05), and Mg co-doping, Zn0.95− y Pb0.05 Mg y O (0≤ y ≤0.05), on the microstructural properties, optical parameters and wettability of ZnO films were investigated. X-ray diffraction (XRD) and field emission-scanning electron microscopy (FE-SEM) results show that the films have polycrystalline and hexagonal structure with a preferred (002) orientation combined with wrinkle network structure for the Pb doped films. The crystalline quality is slightly enhanced with the Pb doping and then deteriorated after Mg co-doping. The influences of the crystallinity and chemical composition on the film wettability are studied. All films show transparency between 85–93%. The reflectance and optical band gap of ZnO films decrease for Pb doping and then increase with Mg co-doping. Well-known Swanepoel׳s method is employed to determine the refractive index ( n ) and film thickness ( d ). The influences of Pb and Mg co-doping on the Urbach energy and optical dispersion parameters are also discussed.